PENGARUH PENDIDIKAN KESEHATAN TENTANG TEKNIK MENYUSUI TERHADAP KETEPATAN TEKNIK MENYUSUI DI DESA PURWOREJO KECAMATAN PUNGGING MOJOKERTO - Mardiyana, Rina; puspita, Ely (JURNAL KEPERAWATAN SEHAT, 2015)
Breastfeeding is giving food to baby directly from the mothers breast. To support successful breastfeeding, good and correct breastfeeding techniques are required. Thus required the provision of health education about good and right breastfeeding technique from health staff. This study aims to determine the effect of health education on breast-feeding techniques with exactness feeding techniques in Purworejo District of Pungging Mojokerto. The population in this study were all breastfeeding mothers of infants aged 0-90 days in Purworejo, District Pungging, Mojokerto. With a sample of all the nursing mothers of infants aged 0-9 days in Purworejo, District Pungging, Kabupaten Mojokerto as many as 24 respondents. The sampling technique that used is total sampling. This study uses a model of One Group Pretest-Posttest Design. Data analysis management using the coding, scoring, tabulating, and cross tabulation. Based on the comparison of before and after, the provision of education showed most respondents do breastfeeding techniques properly. From 4 correct respondents (16.7%), increasing to 10 respondents (41.7%) and of 20 incorrect respondents (83.3%) to be 14 respondents (58%). There were 14 respondents who did not change, this is due to factors such as the anatomy of flat breast nipple. That means there are no influence from Giving Health Education About Breastfeeding Techniques Against Precision Feeding Techniques in Purworejo District of Pungging Mojokerto in women who have breast anatomy that is not physiologicalKeywords: Education Pesehatan, Breastfeeding, Breastfeeding Techniques